Communicating COVID-19 Pandemic on Facebook: Illustrations from Users’ Screenshots from Nigeria and Bangladesh - Habib Mohammad Ali; Herbert Batta; Henry C Ogaraku (Asian Journal of Media and Communication, 2021)
The outbreak of COVID-19 has dented the global public health profile. On the one side, the ubiquity of social media has led to  damaging misinformation, fake news, stigmatization, and conspiracy theories. Fortunately, on the other side, the advantageous characteristics of social media and the informational support mechanisms with which they produce social safety valves; are a solid basis to curbing the pandemic. This paper examines the use of social media as a valuable platform to publicly communicate the COVID-19, especially its scientific discourses. This paper focuses on Facebook as a platform amenable to the strategic digital  communication of COVID-19. It takes illustrations from screenshots of Facebook users in Nigeria and Bangladesh. Some of the identified strategies include supporting for preventive measures, focusing on solutions, countering fake information, standing against racism and  stigmatization, relying on scientific facts, confronting conspiracy theories, dealing with pseudoscience and denials, explaining statistics meaningfully, avoiding the temptation to trivialize and sensationalize, and using local languages.Keywords: social media strategies, science communication, social  support, COVID-19 pandemic.